Preparing the New Phase of Argo: Technological Developments on Profiling Floats in the NAOS Project - André, Xavier; Le Traon, Pierre-Yves; Le Reste, Serge; Dutreuil, Vincent; Leymarie, Edouard; Malardé, Damien; Marec, Claudie; Sagot, Jérôme; Amice, Martin; Babin, Marcel; Claustre, Hervé; David, Arnaud; et al. (Frontiers in Marine Science, 2020)
The international array of profiling floats known as Argo is a major component of the global ocean- and climate-observing system. In 2010, the NAOS (Novel Argo Observing System) project was selected as part of France’s Equipex “Investissement d’Avenir” program. The objectives of NAOS were to consolidate the French contribution to the Argo core mission (global temperature and salinity measurements down to 2,000 m) as well as to develop the future generation of French Argo profiling floats and prepare the next phase of the Argo program with an extension to the deep ocean (Deep-Argo), biogeochemistry (BGC-Argo) and polar seas. This paper summarizes the main technological advances and at-sea validations carried out as part of NAOS: development of a deep (4,000 m) float, a new BGC float for R&D applications, and a BGC float for deployments in Arctic areas; assessment of a new density and Absolute Salinity optical sensor; improvement of the reliability of the standard Argo float; and upgraded satellite-transmission performance.